ChemInform Abstract: Highly Diastereoselective Addition of Alkoxyethynyl Aluminum Reagents to N‐tert‐Butylsulfinyl Aldimines. Issue 31 (5th August 2014) - Verrier, Charlie; Carret, Sebastien; Poisson, Jean‐Francois
Abstract The addition of in situ generated alkoxyethynyl aluminum reagents (II) to sulfinylimines (III) affords alkoxypropargylamines (IV) in high yields and with significant higher diastereoselectivities compared to the reaction of the corresponding lithio acetylides.